Policy and Strategy: for patriotism, institutions and economic development in Nigeria - Onyeisi, Ogbonna (Enugu, Nigeria Focus Projects Ltd, 2019)
The book outlines the lucid ways and means of achieving economic development, through promotion of patriotism and strengthening of institutions
Includes bibliographical references, index
osc 30/11/22
Loans
Keywords: Social Policy; Policy and strategy; Economic Development - social aspect; Nigeria